(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Harmonic (ultracision) Scalpel is a part & parcel of modern Day surgery, Endo-laparoscopic & minimally access surgery. We use this instrument in different minimally access surgeries for the last 5 years. Different open & laparoscopic operations of about 800 cases were performed within this period. Results of our operations with Harmonic Scalpel were very much inspiring, safe and surgeon-friendly with a rapid discharge of the patient from the hospital. The main disadvantages are that the instrument itself is costly & so is its maintenance. It needs a long term practice to be handy. Among open surgeries breast, thyroid, hemorrhoids, tonsils etc. are to be mentioned. In laparoscopic surgery, Harmonic scalpel reduced total operation time in our series. Harmonic scalpel is a laparoscopic surgical instrument that is changing doctors performance as well as decreasing patients recovery time. Although, it is not poor-friendly, but can be used for safe, rapid surgery & patient-friendly operation. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12188 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 25-28